ANALYSIS OF ASSESSMENT METHODS OF THE PROCESS OF MANAGEMENT OF THE ENTERPRISE'S EXTERNAL ECONOMIC ACTIVITY IN THE CONTEXT OF INCREASE IN ITS COMPETITIVENESS - А. Ю. Погребняк; К. О. Щур (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2025)
The article is devoted to the analysis and systematization of methods for assessing the process of managing the foreign economic activity of an enterprise in order to increase its competitiveness. It is substantiated that strategic management of foreign economic activity is an important tool for achieving economic success in international markets, as it allows enterprises to adapt their strategies to the constantly changing external environment, as well as effectively use available resources to expand market positions. Approaches to defining the category of "enterprise competitiveness" are systematized. It is determined that strategic management of foreign economic activity of an enterprise in a competitive environment is a multifaceted and complex process. Its main goal is to develop, implement and effectively implement strategies that contribute to the adaptation of the enterprise to changes in the international business environment and ensure its competitiveness. The authors prove that studying the concept of enterprise competitiveness requires a comprehensive approach that takes into account the dynamic nature of market conditions and the ability of the enterprise to quickly adapt to changes in the external environment. Special methods used only in strategic analysis are systematized, their main content, advantages and disadvantages are determined. Among them are the SPACE method, the LOTS method, PEST analysis (STEP analysis), SWOT analysis, RIMS analysis, and the study of the object profile. The author analyzed examples of successful cases of implementation of modern approaches to foreign economic activity management and innovative solutions. The study confirmed that the competitiveness of an enterprise is a multidimensional category that includes the ability to adapt to dynamic changes in the external environment, introduce innovations, reduce costs, effectively manage resources, and ensure high-quality implementation of marketing and production strategies.